2019
DOI: 10.1097/md.0000000000016121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the aperture and midportion femoral tunnel widening after anterior cruciate ligament reconstruction

Abstract: Background: To identify whether the aperture or the midportion of the femoral tunnel had a larger tunnel widening in patients who undergo ACL reconstruction. Methods: PubMed, EMBASE and Cochrane Library were searched for relative studies that evaluated tunnel widening in patients underwent arthroscopic ACL reconstruction. Two reviewers independently recorded data from each study, including the sample size and magnitude of tunnel widening. Random-effects meta-analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…10 In humans, MRI shows that tunnel widening occurs in the first 6 to 24 weeks, 44 but despite conflicting reports, a systematic review showed no significant difference in femoral tunnel widening between the aperture and midportion in humans. 5 Possible reasons why widening would be greater at the aperture compared with midportion include biological factors such as synovial fluid influx containing osteolytic cytokines 36 and increased graft tunnel motion. 31 In this study, the control group showed greater tunnel widening at the femoral aperture compared with the femoral midportion.…”
Section: Discussionmentioning
confidence: 99%
“…10 In humans, MRI shows that tunnel widening occurs in the first 6 to 24 weeks, 44 but despite conflicting reports, a systematic review showed no significant difference in femoral tunnel widening between the aperture and midportion in humans. 5 Possible reasons why widening would be greater at the aperture compared with midportion include biological factors such as synovial fluid influx containing osteolytic cytokines 36 and increased graft tunnel motion. 31 In this study, the control group showed greater tunnel widening at the femoral aperture compared with the femoral midportion.…”
Section: Discussionmentioning
confidence: 99%
“…6 ORIGINAL PAPER PŮVODNÍ PRÁCE intra-articular orientation of the intact ACL with proper coronal and sagittal obliquity, it might result in a possible increased edge pressure at the FT aperture related to the acute angle between the ACL graft and the FT compared to the transtibial technique. Celik and Lee reported in the meta-analyses that there was no significant difference in FT widening between the aperture and the mid-portion in patients who underwent ACL reconstruction (5). In the biomechanical study, which anatomic double bundle technique through far AM portal was used, Nishimato et al found that, the stress on the FT aperture in the AM portal technique, was not increased as much as transtibial technique (18).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review concluded that no significant difference in TW was found between the aperture and the midportion in patients who underwent ACL reconstruction. 36 Second, in the present study, none of the factors that might affect TW, such as graft-bending angle, position of the bone plug in the tunnel, and tunnel location, were evaluated. Thus, further investigations in larger cohorts using multivariate regression analyses of such factors must be performed in the future.…”
Section: Discussionmentioning
confidence: 99%